Humans, fish, spiders and bees inherited working memory and attention from their last common ancestor - Earl, Brian (Frontiers in Psychology, 2023)
Working memory (WM) is information in the neural systems of mobile animals which is in a state that makes it available to neural processes that select the animals’ responses. WM is essential for all mental processing: finding the way home; solving problems; preparing responses to prey, a potential mate, a predator, or other important matter, even when they are no longer sensed, such as when prey are hidden from sight. Attention is enhanced information relevant to the organism’s current focus—which may be a situation or a planned action—and diminished non-focus information. Attention assists in the identification of objects, and investigation of moving, or unusual objects. It is also associated with the generation of WM. Attention “activates” information—incoming sensory information, or information held in short term or long term memory—and this information becomes WM. Information in WM is available to mental processes, including the processes that control attention, so there is an interaction between WM and attention: Attended information becomes WM, but WM information influences the choice of attentional focus. WM and attention, with generally similar properties, are possessed by humans, archer fish, and other vertebrates; spiders, bees, and other arthropods; and members of other clades, whose last common ancestor (LCA) is believed to have lived more than 600 million years ago. It has been reported that homologous gene groups control the development of vertebrate and arthropod brains, and the brains of members of some other clades. These genes can only have been conserved because the brains whose development they control generate adaptive responses. The active information in WM is necessary for these processes to operate, therefore WM must have evolved prior to brains. It is proposed that WM and attention are widespread because they are phylogenetically conserved mechanisms that are essential to mental processing, and evolved before the LCA of vertebrates and arthropods.